Omnet Sales Digital Protection with Box Jenkins and Delphi Method (case Study: PT Media Virtual Indonesia) - Sarif Hidayat Tullah (Fakultas Teknik Universitas Bhayangkara, 2017)
To be able to develop sales turnover digital newspaper Jawa Pos, PT. Media Virtual Indonesia requires an appforecasting a sales turnover. The method used in forecasting the quantitative turnover using ARIMA method (BoxJenkins) while for forecasting the skin using Delphi method. The results showed ARIMA AR method became an optionbecause it has the smallest MSE error that is ARIMA AR 3525.36963, ARIMA MA 3803.33228, while ARIMA ARMA4176.79443. While with the Delphi method, the main problem is the increase in selling power of Digital Java Posnewspaper, while the results obtained at each stage is Phase 1: Which region will be the concentration of sales:Bandung City with points 7. Stage 2 How to introduce the product to the surrounding community? : Held a LocalEvent.